Homogenisation approach in analysis of creep behaviour in multipass weld. (January 2014) - Lvov, I.; Naumenko, K.; Altenbach, H.
<x content-type="archive" xml:space="preserve">Abstract</x> Different zones of welded joints are subjected to different temperature fields during the process of welding. Furthermore, in multi-pass welding, heating and cooling cycles, which occur due to the overlap of the pass beads, lead to the formation of complex microstructures. A method of evaluating the creep response of a multipass weld based on the micromacro mechanics approach is introduced. Multipass weld microstructures consisting of a columnar zone, which can be related to the microstructure of a single pass weld, and a heat affected zones are considered. To model the microstructure of the multipass weld metal the representative volume element (RVE) method is employed. Numerical tests on one-component loading of the RVEs are performed and creep material properties for equivalent weld material reported for welds with different number of passes.